Die Bibliothek in der Zukunft Regional - Global: Lesen, Studieren und Forschen im Wandel - Niedermair, Klaus; Schuler, Dietmar (innsbruck university press, 2015)
Martin Wieser worked from May 1975 until the end of 2014 at the University and Regional Library of Tyrol, from 1999 until his retirement as its director. Most of those who worked on Austria's library stage during this time will have been met or known to some extent by Martin Wieser. The commemorative treaty dedicated to retiring him spans a wide range of content, from the traditional to the digital library, as well as collaborative projects at regional, national and international levels. Thus, the contributions are essentially to the topics "Librarianship in Tyrol", "Librarianship in Austria", "University and State Library Tyrol", "Book and Library History", "Library Construction", "Library Education", "The Library in Research and Teaching "as well as" Library Management and Library Services ". In addition, there are sketchy, essay-style or slightly more detailed depictions, which either focus on a particular theme or establish a relationship with the celebrated. Finally, Martin Wieser himself summed up his 40-year career in Austrian librarianship in a very personal way in his lecture held at the Association Day 2014 in Graz. The focal points are the conversion of libraries to EDP-based systems and their continuous development in the sense of improving, expanding and optimizing the availability of information.